The Influence Of Perceived Ease Of Use And Perceived Usefulness On The Decision To Use Of Qris As A Digital Payment In Generation Z In The City Of Bandung - Ramdhani, Ardian; Syafitri, Syifa; Rizki Amalia, Dea; Lanfadilan, Kiki; Padillah Ahmad, Alief (Jurnal Bisnis dan Ekonomi, 2024)
This study aims to examine the effect of perceived ease of use and perceived usefulness on the decision to use QRIS as a digital payment for Generation Z in Bandung City. Money, both in paper and metal form, has an important role in economic transactions. However, with the development of financial technology (fintech) technology, payment methods are starting to shift from cash to digital. Quick Response Code Indonesian Standard (QRIS) is a QR code standard implemented to facilitate digital payments in Indonesia. This research uses a quantitative method with a descriptive approach, and data is collected through questionnaires to Generation Z QRIS users in Bandung City. The results showed that perceived ease of use and perceived usefulness have a positive and significant influence on the decision to use QRIS. The practicality and efficiency of QRIS make it popular among Generation Z, who tend to prioritize convenience and usefulness in financial transactions. These findings confirm the importance of perceived convenience and benefits in influencing the decision to use digital payment technology.